Impact of Smartphone-Induced Mental Fatigue on Resistance Training Performance and Efficiency - The Role of Smartphone Use During Workout - Maciąg, Maria; Bieńko, Mateusz; Bieńko, Marta; Marchaj, Magdalena; Putra, Anna; Korta, Karolina; Król, Tomasz; Toborek, Michalina; Niedziela, Natalia; Bednarz, Karolina (Quality in Sport, 2024)
Introduction Resistance training volume is a key determinant of muscle hypertrophy and strength development. However, mental fatigue can significantly impact this volume, ultimately affecting performance. One prominent source of mental fatigue in modern gym environments is smartphone use, which has become pervasive and may reduce workout efficiency and overall training volume. Purpose This review examines the dual effects of smartphone use on resistance training outcomes and offers strategies to balance these impacts effectively. Conclusions Smartphone-induced mental fatigue increases perceived exertion, leading to reduced performance during resistance training by lowering volume-load and endurance, particularly in low- and moderate-intensity exercises. Despite this, maximal strength appears to remain unaffected. Additionally, smartphone use diverts cognitive resources, resulting in mental fatigue and impairing both physical and technical performance due to distractions during workouts. It can also unintentionally prolong rest periods, which disrupts the balance between muscle recovery and mental readiness, further decreasing training efficiency. However, smartphones also offer valuable benefits, such as access to fitness apps, progress tracking, and motivational music, which can help maintain or even enhance performance by improving focus and motivation. To minimize distractions and optimize training outcomes, strategies such as using airplane mode or scheduling specific times for phone use are recommended. While excessive smartphone use can impair training efficiency, careful management and strategic use can enable athletes to capitalize on its benefits and improve resistance training results. Future research should focus on developing best practices for incorporating smartphone use in fitness settings to balance its advantages while minimizing its downsides.